2021
DOI: 10.1038/s41598-021-83147-7
|View full text |Cite
|
Sign up to set email alerts
|

Detection of copy number variation associated with ventriculomegaly in fetuses using single nucleotide polymorphism arrays

Abstract: Etiopathogenesis of fetal ventriculomegaly is poorly understood. Associations between fetal isolated ventriculomegaly and copy number variations (CNVs) have been previously described. We investigated the correlations between fetal ventriculomegaly—with or without other ultrasound anomalies—and chromosome abnormalities. 222 fetuses were divided into four groups: (I) 103 (46.4%) cases with isolated ventriculomegaly, (II) 41 (18.5%) cases accompanied by soft markers, (III) 33 (14.9%) cases complicated with centra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 39 publications
3
14
1
Order By: Relevance
“…Other studies have demonstrated similar results. For example, Shaffer et al (2012) found that the rate of pathogenic CNVs in fetuses with isolated VM and non-isolated VM was 4.0 and 6.6%, respectively; Donnelly et al (2014) reported that the rate of CNVs in fetuses with isolated VM and non-isolated VM was 8.7 and 17.2%, respectively; Wadt et al (2012) reported on two familial submicroscopic terminal 6q deletions in fetuses with isolated VM; Fu et al (2014) found MECP2 microduplication in four fetuses with VM; Xue et al (2021) reported that detections of clinical significant CNVs were higher in non-isolated VM than in isolated VM (16.81% vs. 10.7%, P = 0.19). In the future, large-scale studies are required to determine the relationship between the incidence of genomic abnormalities and the severity of VM in fetuses.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have demonstrated similar results. For example, Shaffer et al (2012) found that the rate of pathogenic CNVs in fetuses with isolated VM and non-isolated VM was 4.0 and 6.6%, respectively; Donnelly et al (2014) reported that the rate of CNVs in fetuses with isolated VM and non-isolated VM was 8.7 and 17.2%, respectively; Wadt et al (2012) reported on two familial submicroscopic terminal 6q deletions in fetuses with isolated VM; Fu et al (2014) found MECP2 microduplication in four fetuses with VM; Xue et al (2021) reported that detections of clinical significant CNVs were higher in non-isolated VM than in isolated VM (16.81% vs. 10.7%, P = 0.19). In the future, large-scale studies are required to determine the relationship between the incidence of genomic abnormalities and the severity of VM in fetuses.…”
Section: Discussionmentioning
confidence: 99%
“…However, 17 (5.1%) cases in the VOUS group feared the uncertainties and stubbornly decided to terminate the pregnancy. Thus, for VOUS foetuses, further long-term follow-up studies, experience accumulation and sharing are necessary [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…CMA was carried out using Affymetrix CytoScan 750 K array (Affymetrix Inc., Santa Clara, CA), and data was analyzed via Affymetrix Chromosome Analysis Suite Software (version 3.1.0.15) as previously described 19 . The reporting threshold was set at gains ≥ 1 Mb, losses ≥ 500 Kb and loss of heterozygosity (LOH) ≥ 10 Mb.…”
Section: Methodsmentioning
confidence: 99%